Morningness-eveningness and amplitude: development and validation of an improved composite scale to measure circadian preference and stability (MESSi) - Randler, Christoph (Chronobiology international, 2016)
Measuring morningness-eveningness is an important aspect of individual differences because it is associated with many aspects of personality and health. The present study outlines recent advancements in the field of measurement and proposes an improved assessment of morningness-eveningness, such as the measurement of circadian amplitude, updating and reflecting new item developments, addressing the clock time based measures, the morning-biased items and the aspect of uni versus multidimensionality. Four studies have been carried out in Germany to present a novel development (with a total sample of N = 1181). In study I, the exploratory factor analysis (EFA) revealed three dimensions, one of morningness, one of eveningness and one of amplitude/stability. Then, items were reduced to present a clearer factor structure by removing ambiguous items. In the second study, a shortened questionnaire was applied, with 15 items (5 per construct), but Confirmatory Factor Analysis (CFA) did not provide acceptable fit indices. Refining items were made in study III, which again showed a clearer factor structure in EFA, and subsequently, in study IV, the refined set of 15 items provided a good fit of a CFA. The final questionnaire was tested for validity by applying clock times, personality questions and alertness ratings. Thus, this newly developed questionnaire contains three distinct dimensions. To reflect the new content, the scale is labelled morningness-eveningness-stability-scale improved (MESSi).